Preparation and Characterisation of ZnO/NiO Nanocomposite Particles for Solar Cell Applications - S. Kerli; Ü. Alver (Journal of Nanotechnology)
The mixture of ZnO and NiO effect on solar cell has been investigated. ZnO and NiO particles were produced by hydrothermal method and the produced particles were annealed at 500°C for 1 hour. Crystal structure and morphological properties of particles were examined by X-ray diffraction (XRD) and scanning electron microscope (SEM). XRD measurements showed that ZnO particles have a hexagonal wurtzite structure and NiO particles have a cubic structure. SEM results show that both ZnO and NiO particles are the form of nanoparticles. Dye-sensitized solar cells were fabricated by N-719 (Ruthenium) dyes and mixing ZnO/NiO particles in different ratios, 100/0, 50/50, and 0/100. It was observed that the solar cells made with ZnO have the highest performance with the efficiency of 0.542%. In addition, it was observed that when amount of NiO ratio increases in the mixture of ZnO/NiO, the efficiencies of DSSCs were observed to decrease.